Estudio del Comportamiento Estructural de Bóvedas y Cúpula de la Estancia Jesuítica Santa Catalina, Provincia de Córdoba, Argentina - Gómez, J. L.; Ruata, M. E.; Nicasio, C.; Klein, K. (Revista ALCONPAT, 2014)
This job shows the study realized to test the dome structural behavior, of Jesuit Santa Catalina´s church and his vault, also novitiate´s vault and one room from the ranch, with demonstrations of fissures. It describe a previously work at analysis tension, including a general 3D survey by a total station, in order to prepare the digital drawings and fundamentally determinate the thickness of the vaults and dome. Also realize two tangential wells to analyze the characteristics of the ground and the deepness of foundations. The sectional verification was made with Algor´s software analysis by very thin element from CAD solid models. The results of these studies allow assessing the safety vaults and dome structure, and propose actions for the preservation and maintenance of this building declared cultural heritage of humanity by UNESCO. Keywords: dome, vaults, heritage, stress analysis